People will talk [videorecording (DVD)] - Mankiewicz, Joseph L.; Mankiewicz, Joseph L.; Grant, Cary, 1904-1986; Crain, Jeanne; Currie, Finlay, 1878-1968; Cronyn, Hume; Slezak, Walter, 1902-1983; Blackmer, Sidney, 1895-1973; Ruysdael, Basil; Locke, Katherine. 1910-1995; Goetz, Curt, 1888-1960 (Twentieth Century Fox Home Entertainment, 2003)
Successful and well-liked, Dr. Noah Praetorius becomes the victim of a witchhunt at the hands of Professor Elwell, who disdains Praetorius's unorthodox medical views and also questions his relations with Mr. Shunderson.